Implications for Child rights amid COVID -19 Pandemic and Economic crisis in Sri Lanka - Raveenthiran Vivekanantharasa; Manotar Tampubolon (Journal of Scientific Research, Education, and Technology (JSRET), 2023)
This article clearly explains about the implications of child rights amid COVID-19 pandemic and economic crisis in Sri Lanka. Among the countries in Asian continent, Sri Lanka is one of the countries that practices good practices to safe guard the rights of children since the attainment of independence from British rulers. The protocols and amendments which are taken to protect rights of children elicit the role of the country in line with safeguarding child rights. Apart from all effective implementations of amendments and protocols of child rights in Sri Lanka, COVID - 19 pandemic and economic crisis have made various implications in the processing to safe guard child rights. How children rights are affected and what type of challenges they faced during those periods are the main objectives of this article and this article clearly explains it. Especially, the challenges faced by students are discussed under four main clusters of child rights, such as the right to survival, the right to protection, the right to development, and the right to participation. Moreover, this article also will illustrate that how these two crisis time have positively impacted on the development of child rights.